MAHASANTRI SATISFACTION TOWARDS THE UNIVERSITY BOARDING SCHOOL: A SERVICE QUALITY APPROACH IN ISLAMIC HIGHER EDUCATION - R. Nadia R.P. Dalimunthe; Dahlya Indra Nurwanti; Siti Nuraeni Muhtar; Nurul Hilaliyah (Islamic Management: Jurnal Manajemen Pendidikan Islam, 2019)
Mahasantri (an Islamic university students) is an agent for Islamic Higher Education Institution to face the Moderate Islam Malay Era. In Indonesia, for example, there is a university boarding school program for Mahasantri to improve their personality and competence. This study is trying to find out whether the program has been aligned with their satisfaction. One of service they received in the boarding is English Language Learning program. They are going to be interviewed about their satisfaction toward the program. Then, the interview result will be analyzed to generate the satisfaction indicator referring to five dimensions of Service Quality (SQ) by Parasuraman and Berry (1991).